Profile of Nontuberculous Mycobacteria and Mycobacterium tuberculosis Detected in the Sputum of Pulmonary Tuberculosis Re-treatment Patients at Dr. Soetomo General Hospital - Mochammad Afif Ziaulhaq; Mertaniasih, Ni Made; Meliana, Resti Yudhawati; Permatasari, Ariani (Institute of Topical Disease Universitas Airlangga, 2025)
Tuberculosis (TB) remains one of the leading infectious diseases worldwide. Despite global efforts to control TB, it remains a major public health issue, affecting 10.6 million people annually in 2021, with significant morbidity and mortality, particularly in resource-limited settings. Effective treatment of TB requires strict adherence to long-term medication, but challenges such as treatment failure, relapse, and loss to follow-up complicate outcomes. This is especially concerning for patients with comorbidities such as diabetes, HIV, or hypertension, which not only increase the risk of TB but also hinder its treatment and elevate the likelihood of nontuberculous mycobacteria (NTM) infections. This study aimed to analyze 326 pulmonary TB retreatment cases at Dr. Soetomo General Academic Hospital from October 2023 to April 2024. The retrospective design identified that 323 cases involved MTB and 3 involved NTM. The findings show that loss to follow-up was the most common reason for retreatment, particularly among males and older adults. Comorbidities were found to exacerbate treatment challenges, with some retreatment cases lasting up to 24 months. The study concludes that loss to follow-up remains a major risk factor for TB retreatment, particularly in MTB cases, and highlights the importance of managing comorbidities to improve treatment outcomes.